2020
DOI: 10.3389/fimmu.2020.584210
|View full text |Cite|
|
Sign up to set email alerts
|

The Role Played by Mitochondria in FcεRI-Dependent Mast Cell Activation

Abstract: Mast cells play a key role in the regulation of innate and adaptive immunity and are involved in pathogenesis of many inflammatory and allergic diseases. The most studied mechanism of mast cell activation is mediated by the interaction of antigens with immunoglobulin E (IgE) and a subsequent binding with the high-affinity receptor Fc epsilon RI (FcεRI). Increasing evidences indicated that mitochondria are actively involved in the FcεRI-dependent activation of this type of cells. Here, we discuss changes in ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 99 publications
(184 reference statements)
1
29
0
Order By: Relevance
“…On the one hand, the activated MCs could facilitate wound healing by recognizing antigens through pattern recognition receptors and the high-affinity immunoglobulin E receptor, resulting in the releasing of granules, which further mediates cell recruitment, fibrosis, angiogenesis, and extracellular matrix deposition ( Ozpinar et al, 2020 ). One the other hand, the cytoplasmic granules from MCs also contribute to multiple inflammatory and allergic pathogenesis diseases, including asthma, allergy, arthritis, interstitial cystitis, irritable bowel syndrome (IBD), ulcers, and prostatitis ( Chelombitko et al, 2020 ; Fu et al, 2020 ). Notably, accumulating studies implicate the role of MCs in CNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the activated MCs could facilitate wound healing by recognizing antigens through pattern recognition receptors and the high-affinity immunoglobulin E receptor, resulting in the releasing of granules, which further mediates cell recruitment, fibrosis, angiogenesis, and extracellular matrix deposition ( Ozpinar et al, 2020 ). One the other hand, the cytoplasmic granules from MCs also contribute to multiple inflammatory and allergic pathogenesis diseases, including asthma, allergy, arthritis, interstitial cystitis, irritable bowel syndrome (IBD), ulcers, and prostatitis ( Chelombitko et al, 2020 ; Fu et al, 2020 ). Notably, accumulating studies implicate the role of MCs in CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells (MCs), one of the granulocytes derived from the myeloid stem cell that widely distributed in tissues surrounding blood vessels, nerves, smooth muscle cells, and synovial membranes, are an important regulator participating in both innate immunity and adaptive immunity ( El Ansari et al, 2020 ). Upon activation, MCs could rapidly migrate to the site of injury and undergo degranulation by releasing the preformed mediators, including tryptase, chymase, histamine, heparin, serotonin, and prostaglandins into extracellular, which further recruit immune cells and amplify the inflammatory response ( Chelombitko et al, 2020 ). For years, MCs have been mainly studied due to their pathogenic role in allergic responses during the progression of urticaria and asthma ( Falduto et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are cellular structures not only responsible for the production of energy necessary for cell metabolism by accumulation of ATP through oxidative phosphorylation, but also the place where genetic material is deposited -methylated mtDNA and unmethylated DNA called the CpG islands (Choi et al, 2020;Liu et al, 2016;West & Shadel, 2017). These organelles are also involved in anabolic and catabolic pathways, including regulation of cell signaling, apoptosis, ROS production, and calcium homeostasis (Chelombitko et al, 2020;Choi et al, 2020;Karmakar et al, 2019;Klein et al, 2020). The role of mitochondria is also related to the immune system, including infectious diseases (Choi et al, 2020;Ren et al, 2020).…”
mentioning
confidence: 99%
“…It has been shown that during infection anabolism is changed into catabolism in immune cells, i.e. in T lymphocytes, including Treg, macrophages M1 and M2 (Chelombitko et al, 2020), neutrophils and mast cells (Chelombitko et al, 2020;Klein et al, 2020), thanks to which mitochondria are involved in molecular mechanisms coordinating energy processes (Chelombitko et al, 2020). Mitochondria in the T effector cells, M1 macrophages and mast cells become fragmented, and in the Treg cells and M2 macrophages they become elongated.…”
mentioning
confidence: 99%
See 1 more Smart Citation